Interaction between Porcine Reproductive-Respiratory Syndrome Virus and Bacterial Endotoxin in the Lungs of Pigs: Potentiation of Cytokine Production and Respiratory Disease - Van Gucht, Steven (American Society for Microbiology, 2003)
Porcine reproductive-respiratory syndrome virus (PRRSV) is a key agent in multifactorial respiratory disease of swine. Intratracheal administration of bacterial lipopolysaccharides (LPSs) to PRRSV-infected pigs results in markedly enhanced respiratory disease, whereas the inoculation of each component alone results in largely subclinical disease. This study examines whether PRRSV-LPS-induced respiratory disease is associated with the excessive production of proinflammatory cytokines in the lungs. Gnotobiotic pigs were inoculated intratracheally with PRRSV and then with LPS at 3, 5, 7, 10, or 14 days of infection and euthanatized 6 h after LPS inoculation. Controls were inoculated with PRRSV or LPS only or with phosphate-buffered saline. Virus titers, (histo)pathological changes in the lungs, numbers of inflammatory cells, and bioactive tumor necrosis factor alpha (TNF-α), interleukin-1 (IL-1), and IL-6 levels in bronchoalveolar lavage fluids were examined. All pigs inoculated with PRRSV-LPS developed severe respiratory disease, whereas the controls that were inoculated with PRRSV or LPS alone did not. PRRSV infection significantly enhanced cytokine production in response to LPS. Peak TNF-α, IL-1, and IL-6 titers were 10 to 100 times higher in the PRRSV-LPS-inoculated pigs than in the pigs inoculated with PRRSV or LPS alone; and the titers correlated with the respiratory signs. The levels of neutrophil infiltration and the pathological changes detected in the lungs of PRRSV-LPS-inoculated pigs resembled those detected when the effects of PRRSV and LPS inoculated alone are combined, but with no synergistic effects between PRRSV and LPS. These data demonstrate a synergism between PRRSV and LPS in the induction of proinflammatory cytokines and an association between induction of these cytokines and disease.